Collaborative Online International Learning (COIL): Bridging Borders in Rehabilitation Education (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Collaborative Online International Learning (COIL) has emerged as a transformative pedagogical methodology, particularly following the 2020 global shift towards digital collaboration. This approach connects students and faculty across different institutions and cultures to design shared, credit-bearing academic experiences integrated directly into health sciences curricula.A successful COIL module typically spans between 5 to 14 weeks and is structured into four primary phases. It begins with team building through icebreaker activities to establish the psychological safety and trust required for open exchange. This is followed by comparative discussions on disciplinary practices and a core collaborative project where mixed international teams engage in interdisciplinary problem-solving. The experience concludes with reflection activities designed to solidify intercultural growth and transform raw interaction into global competency.The implementation of the FTR-105 course collaboration between Hacettepe University and Xavier University (USA) serves as a key case study for this model. Themed “Preventing Health Issues through an Exercise is Medicine Approach”, this 7-week module challenged students to investigate global healthcare systems and access barriers while navigating an 8-hour time difference. Student outcomes were assessed using the Cultural Intelligence Scale (CQS), which measures growth across metacognitive, cognitive, motivational, and behavioural dimensions.For rehabilitation education, COIL is uniquely valuable as it mirrors real-world interprofessional collaboration and builds essential global health literacy. It provides a cost-effective alternative to physical mobility, ensuring that global learning is accessible to all students regardless of financial background. Ultimately, by removing geographical barriers, COIL serves as a ‘multiplier effect’ that prepares future practitioners for the diverse realities of modern healthcare and digital health practices.Keywords: Collaborative Online International Learning (COIL); digital learning; global health; undergraduate health professions education